The thoracolumbar interfascial block with local anesthesia in osteoporotic vertebral compression fractures treated with percutaneous kyphoplasty provides better analgesia compared with local anesthesia alone: A randomized controlled study - Tao, Hong-lei; Zhang, Hang; Jiang, Yun-feng; Fan, Shan-shan; Wang, Hong-wei; Zheng, Ao-te (Frontiers in Surgery, 2023)
Objective: The purpose of this study was to evaluate the safety and efficacy of TLIP block in PKP, and to confirmed that thoracolumbar interfascial block (TLIP block) could further minimize intraoperative pain and postoperative residual back pain on the basis of local anesthesia. Method: From April 2021 to May 2022, 60 patients with osteoporotic vertebral compression fractures (OVCFs) were included in this prospective randomized controlled trial. They received were local anesthesia (group L) or TLIP block on the basis of local anesthesia (group T) before percutaneous kyphoplasty (PKP) procedure. Pain level (visual analogue scale, VAS) and amount of analgesic rescue drugs (parecoxib), operative time, mean arterial pressure (MAP), heart rate (HR) and complications of were assessed and compared between the two groups. Result: Compared with group L, VAS scores were lower in patients receiving the TLIP block when trocar puncture into the vertebral body (7.4±0.7 vs 4.5±0.9, P<0.01), balloon dilatation (6.6±0.9 vs 4.6±0.9, P<0.01), bone cement injection (6.3±0.6 vs 4.3±0.8, P<0.01), soon after surgery (3.5±0.7 vs 2.9±0.7, P<0.01), 24 hours after surgery (2.5±0.8 vs, 1.9±0.4, P<0.01). Residual back pain (1.9±0.9 vs 0.9±0.8, P<0.01) and the incidence of rescue analgesic use (P = 0.02) in group T was also lower than group L. Compared with group L, MAP and HR was lower in group T when trocar puncture into the vertebral body, balloon dilatation, bone cement injection, but there were no statistical differences soon after surgery and 24 hours after surgery. The incidences of bone cement leakage, constipation and nausea were similar between the two groups. No patient had infection, neurologic injuries, breathing depression, sedation, constipation and vomiting in both groups. Conclusion: TLIP block can further minimize intraoperative pain and postoperative residual back pain, reduce perioperative opioid consumption. On the basis of local anesthesia, TLIP block is an effective and safe additional anesthetic method for PKP.